ANALISIS KEBUTUHAN DOKUMEN SISTEM MANAJEMEN MUTU LABORATORIUM KALIBRASI ALAT KESEHATAN TIPE-C BERBASIS SNI/ISO 17025:2017 - Yeni Pertiwi; Kamal Mahmudi (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
The tight competition between testing and calibration laboratories in the era of the industrial revolution 4.0 requires every laboratory to have documentation of a quality management system according to standards. This is necessary so that testing and calibration laboratories are able to apply the Good Laboratory Practices so that they can achieve consistent quality of test results, prevent discrepancies and improve quality. In order to achieve an excellent medical devices testing and calibration laboratory and be able to compete both nationally and globally, it is necessary to have a laboratory management system documentation that is in accordance with standards. For this reason, this study aims to identify the need for documentation of the quality management system for medical devices testing and calibration laboratory type C in accordance with national and international standards. The research method used in this study has 4 stages. The initial stage is a literature study on identifying problems and setting goals. The second stage is literature study for data collection. The third stage is data processing which includes identification of document requirements and identification of business processes. After that, the verification of the results of the analysis of the identification of document requirements is carried out. The results of the identification of document requirements states that at least 291 documents are needed, consisting of 1 quality manual, 55 quality procedure documents, 147 quality form documents, 25 internal and external documents and 63 work instruction documents.